ممارسة الموسيقى الفيلمية من منظور التمثلات الإجتماعية دراسة سيميوسياقية لتيمات موسيقية مختارة من فيلم معركة الجزائر - عبد القادر, عبد العزيز آيت; كلثوم, بلعباسي (roa, 2021)
يسعى هذا المقال إلى إبراز أهم اللحظات الدرامية التي تقوي معنى الواقعي للنسيج الاجتماعي في واقعية المشهد الفيلمي ، حيث يركز كثيرا حول دراسة السياقات السيميائية التي ترتبط علاقتها بين الأداء الموسيقي ، و الخيال الذي يترجم البيئة الاجتماعية و الذي يكون بدوره ملامح هوية المشهد السينمائي ، و من جهة أخرى تهدف هذه الدراسة إلى التعرف عن كيفية الأداء السوسيولوجي من منظور الأداء الموسيقي المدوّن وفق معطيات بحثية نابعة من التمثلات الاجتماعية ، كما يريد إظهار أهمية دور المحاكاة الاجتماعية في سياقها الثقافي ، و التي بدورها تمكن المؤلف الموسيقي للوصول إلى تحقيق جمالية الصورة السمعية وفق تقنيات التلقي في نصية المشهد المرئي . كلمات مفتاحية: الخيال الرمزي - التمثلات الاجتماعية  - الأداء الموسيقي - الفيلم - التوهم  . Abstract: This article seeks to highlight the most important dramatic moments that strengthen the realistic meaning of the social fabric in the reality of the film scene, where it focuses a lot on the study of seminal contexts that relate to the relationship between musical performance, and the imagination that translates the social environment, which in turn is the features of the identity of the film scene, and on the other hand this study aims to learn about the sociological performance from the perspective of music performance recorded according to research data stemming from social representations, and the study  wants to show the importance of the role of simulations, and on the other hand this study aims to identify how to perform sociological science  from the perspective of music performance recorded according to research data stemming from social representations, and also it highlights  the importance of the role of Social simulation in its cultural context, which in turn enables the composer to achieve the aesthetic of the audio image according to the techniques of receiving in the text of the visual scene Keywords : . Symbolic Fiction- Social Representations - Musical Performance - Film - Illusion .